(3JaSjQ CHj GdSYhOs - (3eLghds
(3ChdgG (B:s
(3QOAG HGdJNaja jUObfj HJdNjU GdMb hJbQjQ GdMLI HJhVjMgG hJRjja GdTHgI Efj CNGa Cf jcPHhf hdSGfj dG jWGhYfj YfO GdeMGLI s
(3BNQgG (B:s
(3hCYhP Hc ef afhf GdaJf hGdTQhQ dGSjeG GdGWeFfGf HOGQ GdZQhQ s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc TQja eUWai, SfI?s
Keywords: (3GdJaSjQ hYdhe GdbQBfs